From a far country : Camisards and Huguenots in the Atlantic world - Randall, Catharine, 1957- (University of Georgia Press, 2009)
"In From a Far Country Catharine Randall examines Huguenots and their less-known cousins the Camisards, offering a fresh perspective on the important role these French Protestants played in settling the New World. The Camisard religion was marked by more ecstatic expression than that of the Huguenots, not unlike differences between Pentecostals and Protestants. Both groups were persecuted and emigrated in large numbers, becoming participants in the broad circulation of ideas that characterized the seventeenth- and eighteenth-century Atlantic world. Randall vividly portrays this French Protestant diaspora through the lives of three figures: Gabriel Bernon, who led a Huguenot exodus to Massachusetts and moved among the commercial elite; Ezâechiel Carrâe, a Camisard who influenced Cotton Mather's theology; and Elie Neau, a Camisard-influenced writer and escaped galley slave who established North America's first school for blacks. Like other French Protestants, these men were adaptable in their religious views, a quality Randall points out as quintessentially American. In anthropological terms they acted as code shifters who manipulated multiple cultures. While this malleability ensured that French Protestant culture would not survive in externally recognizable terms in the Americas, Randall shows that the culture's impact was nonetheless considerable"--Jacket.